Effects of Genetic Polymorphisms of Cytochrome P450 Enzymes and MDR1 Transporter on Pantoprazole Metabolism and Helicobacter pylori Eradication. Issue 2 (2nd November 2016) - Karaca, R Ozgur; Kalkisim, Said; Altinbas, Akif; Kilincalp, Serta; Yuksel, Ilhami; Goktas, Mustafa T; Yasar, Umit; Bozkurt, Atilla; Babaoglu, Melih O
Abstract: Pantoprazole is a proton pump inhibitor that is commonly used in the treatment of peptic ulcer disease (PUD) and metabolized by cytochrome P450 (CYP) enzymes CYP2C19 and CYP3A4. Pantoprazole is a substrate for multi‐drug resistance protein 1 (MDR1). Single nucleotide polymorphisms (SNPs) in CYP2C19, CYP3A4 and MDR1 affect enzyme activity or gene expression of proteins and may alter plasma pantoprazole concentrations and treatment success in PUD. In this study, we aimed to investigate the association between genetic polymorphisms in CYP2C19, CYP3A4 and MDR1 and pharmacokinetics of pantoprazole and therapeutic outcome in patients with either Helicobacter pylori ‐associated [H.P.(+)]‐PUD or [H.P.(+)]‐gastritis. The plasma pantoprazole concentrations were determined by using an HPLC method at the third hour after a 40‐mg tablet of pantoprazole administration in 194 newly diagnosed patients with either [H.P.(+)]‐PUD or [H.P.(+)]‐gastritis. Genotyping was performed by using PCR‐RFLP and DNA sequencing. Among patients appearing for follow‐up examination (n = 105), the eradication rate for H. pylori was 82.8% (n = 87). The median pantoprazole plasma concentrations in poor metabolizers (PM), rapid metabolizers (RM) and ultrarapid metabolizers (URM) were 2.07, 1.69 and 1.28 μg/ml, respectively ( p = 0.04). CYP3A4*1G and *22 polymorphisms did not affect plasma pantoprazole concentrations and H. pylori eradication rate. The MDR1 genetic polymorphisms did not affect plasma pantoprazole concentrations. MDR1 3435CC‐2677GG‐1236CC haplotype carriers had lower H. pylori eradication rate (60%) than the remaining subjects (84.9%) while the difference was not statistically significant ( p = 0.07). In conclusion, while CYP2C19 genetic polymorphisms significantly affected plasma pantoprazole concentrations, polymorphisms of CYP2C19, CYP3A4 and MDR1 did not affect H. pylori eradication rates.